2021
DOI: 10.1007/s10479-021-04218-6
|View full text |Cite
|
Sign up to set email alerts
|

Is oil price risk systemic to sectoral equity markets of an oil importing country? Evidence from a dependence-switching copula delta CoVaR approach

Abstract: In this paper, a dependence-switching copula model is used for the first time to analyse the dependence structure between sectoral equity markets and crude oil prices for India, one of the largest oil importing countries. Specifically, we investigate the dependence and tail dependence for four distinctive states of the market, i.e. rising oil prices-rising equity markets, declining oil prices-declining equity markets, rising oil prices-declining equity markets, and declining oil prices-rising equity markets. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…In particular, the authors found strong left and right tails relative to the median of the distribution. This result documents the importance of using quantile-based measures over mean-based measures (Saeed et al, 2021 ; Tiwari et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 54%
“…In particular, the authors found strong left and right tails relative to the median of the distribution. This result documents the importance of using quantile-based measures over mean-based measures (Saeed et al, 2021 ; Tiwari et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 54%
“…It is also found that the exchange rate markets in China and the United States are not as sensitive to the spillover effects of oil price turmoil. AK Tiwari et al analyzed the dependence relationship between the Indian stock market and crude oil prices using the dependence transformation copula model [28]. Dependence and tail dependence are investigated for four states: oil price-rising-stock-rising, oil price-falling-stock-rising, oil price-falling-stock-rising, and oil price-falling-stock-falling.…”
Section: Introductionmentioning
confidence: 99%